Desempenho do modelo global da ionosfera do IGS: avaliação no posicionamento por ponto na região sul do Brasil em período de alta atividade solar - Armendaris, Osvaldo da Costa; Matsuoka, Marcelo Tomio; Camargo, Paulo de Oliveira [UNESP] (Universidade Federal do Paraná (UFPR), Centro Politecnico, 2009)
One of the main drawbacks of the GPS accuracy for L1 users is the error due to ionosphere. This error depends on the total electron content presents in the ionosphere, as well as of the carrier frequency. Some models have been developed to correct GPS observables of the systematic error due to the ionosphere. The model more known and used is the Klobuchar model, which corrected 50-60% of the ionospheric error approximately. Alternatively, IGS (International GNSS Service) also has developed a model called Global Ionospheric Map (GIM). These maps, in format IONEX, are available in the site of the IGS, and one of the applications of them is to correct the GPS observables of the error due to ionosphere. This work aims at evaluating the quality of GPS point positioning using the IGS ionospheric model in the southerm region of Brazil. Tests carried out had shown an average improvement in the horizontal and vertical determination of 44% and 77%, respectively, when GIM is used in the point positioning.
Perfomance of the IGS-Global Ionospheric Model (GIM): Evaluation at the point positioning in southern area of Brazil in a period of high solar activity
Keywords: GPS Positioning; Ionosphere; TEC; GIM; IGS